The anti-rent era in New York Law $x Political aspects, 1839-1865 - McCurdy, Charles W., 1948- (Studies in legal history., 2001)
A chronicle of the largest tenant rebellion in US history, from its beginning in the rural villages of eastern New York in 1839 until its collapse in 1865. The author highlights the manifold ways in which law and politics shaped the pattern of anti-rent violence and the drive for land reform.